2004
DOI: 10.1016/j.biomaterials.2004.01.041
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication and characterization of linearly oriented nerve guidance scaffolds for spinal cord injury

Abstract: Strategies to promote axonal extension through a site of injury, including the provision of nervous system growth factors and supportive substrates, produce growth of axons, that is highly random and does not extend past the lesion site and into the host tissue (Brain Res. Bull 57 (6) (2002) 833). Physically guiding the linear growth of axons across a site of injury, in addition to providing neurotrophic and/or cellular support, would help to retain the native organization of regenerating axons across the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 18 publications
3
148
1
Order By: Relevance
“…The biocompatibility of PHEMA has been recognized as a potential problem in CNS repair studies. Benefits improves neuronal survival [96] Potentially increases axonal growth [97] Biocompatible; thermal gelling; improves neurite extension [104,105] ; flexible and stable in culture conditions [106] Enhances cell resistance to oxidative stress [108] ; increases neuronal regeneration [108] ; negatively charged [109] ; biocompatible; biodegradable Directs stem cells to a neuronal lineage [111] Promotes axon regeneration across injury site [113] FDA-approved for use in brain, non-toxic, thermally sensitive, functionalizable…”
Section: Synthetic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility of PHEMA has been recognized as a potential problem in CNS repair studies. Benefits improves neuronal survival [96] Potentially increases axonal growth [97] Biocompatible; thermal gelling; improves neurite extension [104,105] ; flexible and stable in culture conditions [106] Enhances cell resistance to oxidative stress [108] ; increases neuronal regeneration [108] ; negatively charged [109] ; biocompatible; biodegradable Directs stem cells to a neuronal lineage [111] Promotes axon regeneration across injury site [113] FDA-approved for use in brain, non-toxic, thermally sensitive, functionalizable…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…HA) [107] ; biologically inert unless modified [106] Low cell adhesion without addition of functional groups (i.e. RGD) [110] Increased astrocyte infiltration [112] Not gel-forming, incompatible with contusion (PHPMA) PHPMA is non-biodegradable but has better biocompatibility than PHEMA because of its modified chemical structure [116] .…”
Section: Limitationsmentioning
confidence: 99%
“…In this study, the effect of scaffolds with different complex structure was studied, demonstrating that open-path designs better promoted axonal regeneration, while closed designs resulted in the encapsulation of fibrous tissues and the enlargement of defects. Freeze-drying is another way to fabricate uniaxial hydrogel scaffolds [37,38]. With a gradient in temperature, scaffolds with honeycomb structure were created [38].…”
Section: Architecturementioning
confidence: 99%
“…The solid-liquid separated solution was subsequently freeze dried. Stokols and Tuszynski also used a uniaxial thermal gradient with agarose to form linear channels (Stokols and Tuszynski 2004). These channels were continuous for up to 1cm and had pore sizes (channel diameter) on the order of 30-100m.…”
Section: Phase Separation and Selective Dissolutionmentioning
confidence: 99%
“…Other studies with hydrogels have shown promising outcomes. Stokols et al reported a unique agarose guidance scaffold consisting of long linear channels (Stokols and Tuszynski 2004). These constructs had pore diameters (channels) of 119±26m and were capable of sustained growth factor release.…”
Section: Nervous Systemmentioning
confidence: 99%